The Rabbit Costal Cartilage Reconstructive Surgical Model - Badran, Karam W.; Waki, Curt; Hamamoto, Ashley; Manz, Ryan; Wong, Brian J. F. (Facial Plastic Surgery, 2014)
Rib grafts in facial plastic surgery are becoming more frequently used. Small animal models, although not ideal may be used to emulate costal cartilage-based procedures. A surgical characterization of this tissue will assist future research in the selection of appropriate costal segments, based on quantitative and qualitative properties. The objective of this study is to assess the surgical anatomy of the rabbit costal margin and evaluate costal cartilage for use in either in vivo or ex vivo studies and to examine reconstructive procedures. Detailed thoracic dissections of 21 New Zealand white rabbits were performed post-mortem. Costal cartilage of true, false, and floating ribs were harvested. The length, thickness, and width at proximal, medial, and distal locations of the cartilage, with perichondrium intact were measured. Further qualitative observation and digital images of curvature, flexibility, and segmental cross-sectional shape were recorded. The main outcome measure(s) is to characterize, describe, and assess the consistency of dimensions, location, and shape of costal cartilage. In this study, 12 to 13 ribs encase the thoracic cavity. Cartilage from true ribs has an average length, width, and depth of 23.75 ± 0.662, 3.02 ± 0.025, and 2.18 ± 0.018 mm, respectively. The cartilage from false ribs has an average length, width, and depth of 41.97 ± 1.48, 2.00 ± 0.07, 1.19 ± 0.03 mm, and that of floating ribs are 7.66 ± 0.29, 1.98 ± 0.04, and 0.96 ± 0.03 mm. Rib 8 is found to be the longest costal cartilage (49.10 ± 0.64 mm), with the widest and thickest at ribs 1 (3.91 ± 0.08 mm) and 6 (2.41 ± 0.11 mm), respectively. Cross-sectional segments reveal the distal cartilage to maintain an hourglass shape that broadens to become circular and eventually ovoid at the costochondral junction. The New Zealand white rabbit is a practical source of costal cartilage that is of sufficient size and reproducibility to use in surgical research where the long-term effects of operations, therapies, devices, and pharmacologic on cartilage can be studied in vivo.
Keywords: costal cartilage; rabbit costal cartilage; cartilage graft; cartilage length; cartilage volume; animal model for facial surgery